Design Whatsapp Gateway Admissions for New Students at Labuhanbatu University During The Pandemic - Mutiara Br Samosir; Rahel Marianti Ritonga; Febriani Naibaho; Ibnu Rasyid Munthe (Jurnal Mantik, 2021)
Over time there will always be many changes that continue to occur, from the smallest things to the biggest things. Especially in this era of increasingly sophisticated technology, getting information is very easy, but during a pandemic like now it is very difficult to carry out activities so that it becomes something very complicated, especially for students who want to enter. registering for college will be very difficult to get information, but fortunately now there is a Whatsapp Gateway that makes it easy for new students to get the latest information about student registration, we are currently conducting research on the Whatsapp Gateway, to make it easier for new students to get the latest information, at this time we use the research method we use today is the waterfall method or the waterfall flow method, this research model works according to stages such as from the highest point to the lowest working according to the correct sequence and process, with the aim of writing this research so that new students can use the Whatsapp Gateway well, making it easier for them to get information. About registration during this covid19 pandemic, which is difficult to carry out daily activities with the Whatsapp Gateway. All that can be done easily, with the Whatsapp Gateway, having an impact on students. prospective new students don't have to worry about how to get the right information, prospective students no longer need to bother coming to campus to see the development of existing information, just use the Whatsapp Gateway, any activity or desire they want to get development information can be done easily only by using the Whatsapp Gateway without having to waste time and energy, everything can be done at home, according to the current rules during this pandemic.